Герой иного времени: [роман] / Анатолий Брусникин - Брусникин Анатолий (АСТ, 2010)
Экземпляры: Аб (20130918) / Инвентарный номер: 100070 / Цена: 111.00 / Авт.знак: Б 89 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6